2021
DOI: 10.7759/cureus.18970
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric Burns of the Hand: Our Experience Over Three Years

Abstract: Background and aimContact burn injuries to the hand are common in the paediatric population, with the most common aetiology involving touching hot surfaces in the household. The hand is also often involved in paediatric scald injuries. The aim of this study was to determine the different presentations of hand burn injuries and analyse the outcomes in the paediatric population at Royal Aberdeen Children's Hospital (RACH). MethodsAnonymised clinic data for paediatric patients with hand burns presenting to our bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Males and preschoolers were most of the burn injury presentations in this retrospective study. Similar results have been previously reported in developed countries 12 18 19. Toddlers and preschool children are often seen to be exploring their world with little understanding for their own safety.…”
Section: Discussionsupporting
confidence: 86%
“…Males and preschoolers were most of the burn injury presentations in this retrospective study. Similar results have been previously reported in developed countries 12 18 19. Toddlers and preschool children are often seen to be exploring their world with little understanding for their own safety.…”
Section: Discussionsupporting
confidence: 86%
“…Despite this, the patient left a ward specializing in burn injuries treatment after 11 days, which can be explained (for example) by good prehospital treatment and fast reaction, because the short time of tissue hypoperfusion enhances the chances of patient survival and smaller cosmetic defect 14 . On the other hand, in the pediatric population, the correlation between prolonged hospitalization and shorter healing period was questioned among all patients with burn injuries 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Hands are a common body area affected by burns, reportedly the commonest [34], especially in children under the age of 5 years [61]. US and Australian papers have found that contact burns are a common source of hand burns (61.4-75.5%) [17,66], with the majority occurring on the palmar aspect of the hand [67,68] affecting either the palm only or the fingers [69]. Hand burns are particularly common in children, with toddlers being at a high risk of sustaining palmar contact burns from touching hot objects out of curiosity and lack of caution [70].…”
Section: Body Area Affectedmentioning
confidence: 99%
“…Hand burns are particularly common in children, with toddlers being at a high risk of sustaining palmar contact burns from touching hot objects out of curiosity and lack of caution [70]. Two studies in HICs found that the most common aetiology of hand burns was contact with a hot stove or oven [67,69], and fireplaces, irons and campfires are other common causes [67]. Friction burns from exercise treadmills are also a common mode of hand injury, accounting for 25% of hand burns over a 5 year period at a US level 1 paediatric burn centre and primarily occurring in the 0-4 age group [66].…”
Section: Body Area Affectedmentioning
confidence: 99%